Copper Tolerance of Trichoderma koningii Tk10 - Kehe Fu; Lili Fan; Jiaming Ji; Xiayu Qiu (Microbiology Research)
Copper (Cu) is an essential micronutrient for all living organisms, serving as a cofactor for numerous enzymes. However, excessive copper concentrations can be harmful. To investigate copper tolerance in fungi, a copper-tolerant strain was isolated from soil and identified as Trichoderma koningii Tk10, with optimized culture conditions being established. Additionally, copper-related genes were analyzed through whole-genome sequencing. The results indicated that Tk10 exhibits a maximum copper tolerance of 5.4 mmol/L and a maximum adsorption rate of 51.5% under optimal cultivation conditions. Whole-genome sequencing revealed six genes associated with copper tolerance, including one superoxide dismutase gene, one peroxidase gene, and three catalase genes linked to copper stress. Furthermore, the enzyme activities of the catalase, superoxide dismutase, and peroxidase significantly increased, reaching levels that were 8.02, 4.12, and 3.88 times higher than those observed in the control group, respectively. A real-time quantitative PCR analysis indicated that three of these genes were significantly upregulated in response to copper stress. The findings of this study provide valuable insights into copper tolerance in filamentous fungi.